2001
DOI: 10.1111/j.1527-3466.2001.tb00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Ifetroban Sodium: An Effective TxA2/PGH2 Receptor Antagonist

Abstract: This review presents a comprehensive discussion on the chemistry, pharmacokinetics, and pharmacodynamics of ifetroban sodium, a new thomboxane A 2 /prostaglandin H 2 receptor antagonist. Thromboxane A 2 is an arachidonic acid product, formed by the enzyme cyclooxygenase. In contrast to other cyclooxygenase products, thromboxane A 2 has been shown to be involved in vascular contraction and has been implicated in platelet activation. In general, results of clinical studies and animal experiments indicate that hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…According to the results obtained from this study, plasma levels of TXA2 was found to be significantly higher in stroke patients (p<0.05) which is similar to the work of [18]. Stroke has been found to be associated with hyperaggregability of platelets and increased thromboxane A2 levels in blood, urine, and tissues.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…According to the results obtained from this study, plasma levels of TXA2 was found to be significantly higher in stroke patients (p<0.05) which is similar to the work of [18]. Stroke has been found to be associated with hyperaggregability of platelets and increased thromboxane A2 levels in blood, urine, and tissues.…”
Section: Discussionsupporting
confidence: 84%
“…World health organisation in collaboration with the world heart federation and the world stroke organisation. 2011;3- 18…”
Section: Resultsmentioning
confidence: 99%
“…The drug was administered daily as a bolus via intragastic tube at a dose of 3 mg/kg. At the dose administered, intestinal absorption of the drug is over 85% and it retains antagonism of thromboxane A2/prostaglandin endoperoxide (TP)‐receptor‐dependent responses for at least 24 hours after oral administration (Ogletree et al., ; Rosenfeld et al., ). Ifetroban is devoid of any agonistic activity.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, PP2 was also capable of inhibiting cellular migration in a Transwell assay (Figure 7A). Previous studies have suggested that thromboxane A2 receptor (TBXA2R) is involved in the migration and invasion of breast cancer cells [27,28] and that isoprostanes may also regulate the activation of TBXA2R [13].To determine if this signaling pathway was affected by PF1, a Transwell migration study was performed with a specific inhibitor (ifetroban) of TBXA2R [29]. We show that inhibition of this pathway by ifetroban was associated with reduced cellular migration (Figure 7B).…”
Section: Pf1 Inhibits Fbs-stimulated Wound Healing and Transwell Migration Of Mda-mb-231 Cellsmentioning
confidence: 64%